Yield and Quality of Pacific white shrimp Litopenaeus vannamei (Boone, 1931) in response to different Killing Methods - Bhat, T. H.; Aman Hassan, Md.; Chouksey, M. K.; Balange, A. K.; Nayak, B. B. (Fishery Technology, 2018)
The present study compares the differences in the effect of two methods of slaughtering i.e. by cold shock in ice water slurry (hypothermia) and by taking out of water (asphyxia) on the quality of white shrimp (Litopenaeus vannamei). Yield, proximate composition, pH, calcium ATPase activity, texture and colour parameters were compared. No significant differences were found in the yield, proximate composition, pH and calcium ATPase activity between the shrimp killed by the two different methods. Texture and colour were found to vary significantly (p<0.05). Texture parameters such as hardness (6900.80±484.93 g), resilience (0.45±0.02), springiness (0.83±0.02) and chewiness (2502.50±148.69) of shrimp killed by hypothermia were found to be better than the shrimp killed by asphyxia (hardness 6144.90±456.74, resilience 0.35±0.01, springiness 0.77±0.02 and chewiness 1803.50±154.64). Similarly colour of the shrimp killed by hypothermia was found to be better than that killed by asphyxia. Therefore it can be concluded that the ice- water immersion method is better for the killing of pacific white shrimp L. vannamei as far as texture and colour are concerned.